Validity and Reliability of Chemical Test Instruments for Acid and Base Solutions Oriented Generic Skills Science (Universitas Negeri Semarang, 2022)
The 2013 curriculum prioritizes the generic skills needed in science learning. Generic science skills require valid and reliable measuring tools. The purpose of this research is to reveal validity and reliability Chemical test instruments oriented to generic science skills on acid and base solutions. The subjects used were 35 students for the small class test and 125 students for the large class test. The method used is the quantitative method in the form of questionnaire sheets and KGS-oriented acid-base chemistry questions. Construct validity using confirmatory first order analysis. Interterrater reliability using 3 raters and tested using two-way annova with Ebel formula. The reliability of the large class test used the cronbach alpha formula. content validity of each item in each 81.25% eligible category. Construct validity seen from the item polarity of the items has a positive Point Measure Correlation (Pt. Mea-Corr). A total of 32 items have a strong or high correlation number. Three questions, namely item number 23 (0.57), 27 (0.49), and 33 (0.67) have a moderate correlation. Reliability between expert raters was analyzed using the Ebel formula resulting in 0.79 which was in the currently category. Small class test reliability 0.97 high category. The reliability of the large class test item reliability is 0.90, personal reliability is 0.94, and the KR-20 is 0.99 which is classified as high. Thus, the level of generic science ability that has been tested for validity and Reliability can be used by educators to determine the level of students' generic science abilities.